Metode Dakwah Majelis Dzikir Rohmatan Lil`alamin Kepada Jama`ah Dalam Menanamkan Nilai Ketauhidan Di Desa Banggle-Kediri - Anjeli; Slamet, Moh. (Menara Tebuireng, 2024)
Abstract— In this study, there are 2 (two) questions that will be answered. These questions: 1). The Da'wah Method of Majlis Dhikr in instilling the value of monotheism and 2). The impact of the practice of dhikr for pilgrims. This study uses qualitative research, with the type of approach used is a case study. Meanwhile, the data analysis technique. The results of the study show that the dhikr da'wah method of the Rohmatan Lil'alamin Assembly can be answered, that the application of dhikr is the key to the success of da'wah among the congregation, through several preliminary stages, implementation stages, and closing stages, as well as follow-up stages. These steps have been implemented well and felt by the congregation, such as feelings of calm, serenity, not stress, and feeling at home in the learning of the dhikr assembly. Keyword: Application of the Dhikr Method, Jamaah, Dhikr, Islamic Values